Hana's Character as Dramatic Trigger in The Film Falling in Love Like in The Movies Works by Yandi Laurens - Aisy, Ghirahani Rihaddatul (Kirana Publisher (KNPub), 2025)
This film has two discussions about love and life problems as you want to be like in the movies. Sometimes we wish that falling in love like in the movies is a dream, so we try to fall in love as best for the best ending as well. As in an uncertain life, problems come as if they are never invited at all. Movies can create and present the character of a person in which the movie was made. So watching the film is not only enjoying the story that is told, but at the same time being able to learn how the reactions of the characters in the film are produced. Falling in Love Like In Movies is one example of a film that features characters so that it can be a trigger and reinforcement in a film drama.